The Bretton Woods institutions and the quest for development in Africa - Zekeri Momoh (Department of Government Studies Universitas Muhammadiyah Makassar, 2023)
The role of the Bretton Woods Institutions in Africa has been subjected to intense debate in the literature of International Relations. This is so particularly because of the implications of the Bretton Woods Institutions on the political and economic activities in Africa. The data for this study were collected from secondary sources such as textbooks and journal articles while content analysis was used to analyse the data collected. The